The Story “In the Summer of 190*” by Alexander Beklemishev is a Literary Hoax by Samuel Kissin (Muni) - Ani Petrs (Studia Litterarum)
The article is devoted to the literary hoax of Samuel Kissin (Muni) (1885–1916), a poet, critic and translator. Based on the material of the memoirs of contemporaries (in particular, V. Khodasevich), archival sources and comments on them the article examines the history, goals and reasons of the hoax created by Kissin — Alexander Beklemishev, on whose behalf S. Kissin wrote poetry and prose, and more than that — in which he tried to reincarnate. The basis of the A. Beklemishev’s novel “In the Summer of 190*” (1907–1908) is “Goliadkin inside out,” the story of the displacement of one person by another from his body, told in the first person. The author of the article pays special attention to the subject organization of the story, the peculiarities of the voices of the authors-narrators, their correlation with each other. Also she highlights The main themes and motifs of the novel and draws parallels between the characters of A. Beklemishev (S. Kissin) and the characters of F. Dostoevsky. In conclusion the article states that the main feature of literary hoax is the construction of another author’s instance.